2017
DOI: 10.5194/tc-2017-7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snowfall in the Alps: Evaluation and projections based on the EURO-CORDEX regional climate models

Abstract: Abstract. Twenty-first century snowfall changes over the European Alps are assessed based on high-resolution regional climate model (RCM) data made available through the EURO-CORDEX initiative. Fourteen different combinations of global and regional climate models with a target resolution of 12 km, and two different emission scenarios are considered. A newly developed method to separate snowfall from total precipitation based on near-surface temperature conditions and accounting for subgrid topographic variabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Kotlarski et al, 2014;Prein et al, 2015). Other studies describing evaluation of different important near-surface variables in 30 the EURO-CORDEX RCMs in the recent past climate include those of Smiatek et al (2016); Knist et al (2016) and Frei et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Kotlarski et al, 2014;Prein et al, 2015). Other studies describing evaluation of different important near-surface variables in 30 the EURO-CORDEX RCMs in the recent past climate include those of Smiatek et al (2016); Knist et al (2016) and Frei et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Table 6 further shows a strong decrease in R (by 2090, -12.0 ± 3.4% for RCP2.6, -17.7 ± 8.1% for 5 RCP4.5 and -37.3 ± 7.3% for RCP8. 5, compared to 1986-2005), with values very similar to Frei et al (2017).…”
mentioning
confidence: 52%
“…The threshold itself and the corresponding linear range highly depends on the hydroclimatic characteristics and thus can strongly vary in space (Liu et al, 2018). It has been shown that more sophisticated approaches using logistic regression for characterizing this range can provide better results (Frei, 2016). In principle such an approach could be included into the hydrological model, but such an implementation is out of scope of this analysis.…”
Section: Discussionmentioning
confidence: 99%